2018
DOI: 10.1245/s10434-018-6601-8
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Breast Cancer-Related Lymphedema (BCRL) Through Prospective Surveillance Monitoring Using Bioimpedance Spectroscopy (BIS) and Patient Directed Self-Interventions

Abstract: Our results demonstrated that early conservative intervention for breast cancer patients high risk for BCRL who were prospectively monitored by utilizing BIS significantly lowers rates of BCRL. These findings support early prospective screening and intervention for BCRL. Early detection with patient-directed interventions improves patient outcomes and decreases the risk of persistent BCRL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 24 publications
4
43
0
5
Order By: Relevance
“…17,[21][22][23][24][25][26] When fluid accumulates and remains in the affected limb, inflammatory and hemodynamic changes increase in severity, 27 and early intervention may prevent or delay progression. Similarly, Kilgore and colleagues 30 reported that only 6% of 146 patients developed chronic lymphedema after early intervention, supporting the observations of Whitworth and colleagues. Similarly, Kilgore and colleagues 30 reported that only 6% of 146 patients developed chronic lymphedema after early intervention, supporting the observations of Whitworth and colleagues.…”
Section: Introductionsupporting
confidence: 56%
See 2 more Smart Citations
“…17,[21][22][23][24][25][26] When fluid accumulates and remains in the affected limb, inflammatory and hemodynamic changes increase in severity, 27 and early intervention may prevent or delay progression. Similarly, Kilgore and colleagues 30 reported that only 6% of 146 patients developed chronic lymphedema after early intervention, supporting the observations of Whitworth and colleagues. Similarly, Kilgore and colleagues 30 reported that only 6% of 146 patients developed chronic lymphedema after early intervention, supporting the observations of Whitworth and colleagues.…”
Section: Introductionsupporting
confidence: 56%
“…Indeed, Whitworth and colleagues 28,29 observed that, of 93 high-risk patients who underwent axillary lymph node dissection and were managed with prospective surveillance, only 3% required additional therapies or had evidence of chronic BCRL over a median 2 years of follow-up. Similarly, Kilgore and colleagues 30 reported that only 6% of 146 patients developed chronic lymphedema after early intervention, supporting the observations of Whitworth and colleagues.…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…Other high-risk groups included populations receiving axillary node radiation and taxane chemotherapy. 22 , 23 In all PSM studies, interventions were initiated when subclinical lymphedema was detected either by BIS L-Dex scores of ≥10 22–25 or a 3% increase from preoperative volume using perometry ( Suppl. Tab.…”
Section: Prospective Surveillance Model and Identified Subclinical (Imentioning
confidence: 99%
“…A new standard of practice in cancer care is warranted because of the improvement in outcomes evident when exercise is integrated into cancer care from diagnosis through treatment. The value proposition of prospective personalized exercise clinical pathways in oncology is that they promote early detection of physical decline and prompt exercise interventions that mitigate or ameliorate many cancer treatment–related symptoms, reduce impairment and disability, 83,84 enhance return to work and social roles, 85,86 and positively influence health endpoints such as infection rates, hospitalization rates, and chemotherapy tolerability in some populations 87‐89 . The proposed 5 domains offer a framework for efficient and effective screening that enables exercise referrals best suited to an individual's existing and evolving needs.…”
Section: Integration To Practice: a Call To Actionmentioning
confidence: 99%